FAKTOR â FAKTOR YANG MEMPENGARUHI KEMAUAN UNTUK MEMBAYAR PAJAK WAJIB PAJAK ORANG PRIBADI - Melina Romilda, 09.05.52.0195; Badjuri, Achmad (Students Journal of Accounting and Banking, 2013)
This study aims to analyze the effect of consciousness pay taxes, knowledge and understanding of tax laws, a good perception of the effectiveness of the tax system, the service tax authorities, financial penalties against the willingness to pay taxes on individual taxpayers KPP Pratama East Semarang. The population in this study is the individual taxpayers registered in LTO East Semarang. Sampling was done using purposive sampling method and sample size 125 respondents. The primary data collection method used was a questionnaire method. Data analysis using multiple linear regression models. The results showed that: Awareness pay tax no significant negative influence on the willingness to pay taxes a while, Knowledge and understanding of tax laws, a good perception of the effectiveness of the system of taxation, service tax authorities and penalties significant positive effect on the willingness to pay taxes. Keywords: Awareness pay taxes, Knowledge and understanding of tax laws, a good perception on the effectiveness of the tax system, the service tax authorities, and financial penalties.